2011
DOI: 10.1172/jci42928
|View full text |Cite
|
Sign up to set email alerts
|

Hunk is required for HER2/neu-induced mammary tumorigenesis

Abstract: Understanding the molecular pathways that contribute to the aggressive behavior of human cancers is a critical research priority. The SNF1/AMPK-related protein kinase Hunk is overexpressed in aggressive subsets of human breast, ovarian, and colon cancers. Analysis of Hunk -/-mice revealed that this kinase is required for metastasis of c-myc-induced mammary tumors but not c-myc-induced primary tumor formation. Similar to c-myc, amplification of the proto-oncogene HER2/neu occurs in 10%-30% of breast cancers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(85 citation statements)
references
References 94 publications
(125 reference statements)
4
81
0
Order By: Relevance
“…Although Hunk has previously been implicated in mammary tumorigenesis as well as metastasis, a physiological role for this kinase has not been defined (2,3,5). We now demonstrate that Hunk maintains the balance between cell survival and cell death during mammary gland development by suppressing the upregulation of myc that normally occurs during postlactational involution.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Although Hunk has previously been implicated in mammary tumorigenesis as well as metastasis, a physiological role for this kinase has not been defined (2,3,5). We now demonstrate that Hunk maintains the balance between cell survival and cell death during mammary gland development by suppressing the upregulation of myc that normally occurs during postlactational involution.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, we demonstrated that Hunk is required for the survival and growth of HER2/neu-driven tumor cells as a consequence of Hunk-dependent regulation of p27 kip1 protein levels and subcellular localization (3). Hunk also reportedly promotes the survival of PC12 neuronal cells, although the underlying mechanism has not been elucidated (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to use m/tomND transgenic mice with spontaneous mammary gland tumors as a model for testing, because they are closer to the native than the xenografted tumor model. We used HER2/neu expression controlled by doxycycline administered through the drinking water to develop a mouse tumor model (m/tomND transgenic mice) in which myc expression could be manipulated (37,38). These mice spontaneously grow mammary gland tumors in a few weeks, and myc expression in the tumors was upregulated by 2-fold under doxycycline-triggered myc upregualtion (Alveraz and Chodosh, unpublished data, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…16.1 ) of breast cancer cells are not completely understood (Lee et al 2010 ;Deng et al 2010 ;de Graauw et al 2010 ;Araki et al 2010 ;Singh et al 2010 ) . Analysis of Hunk (−/−) mice revealed that this Kinase is required (Yeh et al 2011 ) for metastasis of c-myc-induced mammary tumors, but not c-myc-induced primary transformed cells.…”
mentioning
confidence: 99%